Laserterapia na recuperação do olfato e paladar de pacientes com manifestações clínicas residuais do Covid-19 - Bastiani, Felipe Gustavo de (2025)
Covid-19, caused by the SARS-CoV-2 virus, is a highly transmissible and serious respiratory infection, with clinical manifestations ranging from asymptomatic to critical conditions and affected millions globally, with 39 million cases and 715 thousand deaths in Brazil until January 2025. Olfactory disorders, such as anosmia and ageusia, are common symptoms of the infection, affecting up to 82% of those infected. These disorders, in addition to compromising quality of life, represent a risk of accidents and social impacts. Low-intensity laser therapy represents one of the possible therapeutic approaches that can be used, although its effectiveness in treating post-Covid-19 anosmia requires further investigation to optimize an individualized therapeutic protocol. This study aims to evaluate the effect of laser therapy on the recovery of smell in patients with post-Covid-19 residual anosmia, with the expectation of contributing to the improvement of therapeutic strategies and treatment protocols. This is a planned clinical trial, with a convenience sample, involving patients with post-Covid-19 residual anosmia. The inclusion criteria were patients over 18 years of age, with long Covid, that is, residual symptoms 3 months after SARS-CoV-2 infection. Exclusion was applied to patients without olfactory symptoms, with other causes of smell loss, or undergoing treatment for olfactory recovery. The active search for patients was carried out in medical records at the Hospital Universitário do Oeste do Paraná and in Primary Health Care in the city of Cascavel, with 172 patients identified and invited to participate, of which 17 completed the research. Participants participated in the Free and Informed Consent Form, underwent smell threshold tests and odor identification, a self-assessment test on smell and blood collection for analysis of inflammatory markers (IL-6, EL-10 and TNF-α). Participants were divided into two groups: treatment and control, using the Research Randomizer platform. The treatment protocol consisted of 5 laser therapy sessions, 48 hours apart, using a gallium-aluminum-arsenic diode laser at infrared wavelength. The control group underwent the same protocol, but the device had a sealed tip. Data were analyzed with the GraphPad Prism 8.0.2 software, using the Shapiro-Wilk and Wilcoxon tests, and paired and unpaired t-tests according to data normality. The analysis included clinical variables, such as age, sex, duration of symptoms and intensity of manifestations, focusing on the comparison between the treatment and control groups. The results showed a predominance of the age group from 20 to 39 years old (58.82%) and a significant difference only for the treatment group in the following variables: Smell threshold tests and odor identification and self-assessment; and for the control group in the variation of serum levels of TNF-α, initial versus final. The analyzes indicate that laser therapy can have a positive role in the recovery of the sense of smell in patients with anosmia or hyposmia resulting from long Covid and also opens up avenues for future investigations by bringing statistically significant results even with doses and number of sessions lower than those found in the available literature.